2021
DOI: 10.1101/2021.09.22.461292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of community efforts to advance computational prediction of protein-protein interactions

Abstract: Comprehensive insights from the human protein-protein interaction (PPI) network, known as the human interactome, can provide important insights into the molecular mechanisms of complex biological processes and diseases. Despite the remarkable experimental efforts undertaken to date to determine the structure of the human interactome, many PPIs remain unmapped. Computational approaches, especially network-based methods, can facilitate the identification of new PPIs. Many such approaches have been proposed. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…At the same threshold SPA unveils an additional 63 synaptic polarities, altogether identifying 112 polarities at 95% precision, as illustrated in Figure 2F. Our findings indicate that signed extensions of link prediction methods, [28] as well as the growing body of network sign prediction methods [29][30][31][32] should be further explored.…”
Section: Connection To Network-based Sign Predictionmentioning
confidence: 71%
“…At the same threshold SPA unveils an additional 63 synaptic polarities, altogether identifying 112 polarities at 95% precision, as illustrated in Figure 2F. Our findings indicate that signed extensions of link prediction methods, [28] as well as the growing body of network sign prediction methods [29][30][31][32] should be further explored.…”
Section: Connection To Network-based Sign Predictionmentioning
confidence: 71%
“…By being freely accessible and using standard identifiers for proteins, B4PPI can be used by any researcher working on in silico PPI prediction to investigate the inference mechanisms of their models. Contrary to previous benchmarking efforts [18], which it can complement, B4PPI leverages large professionally curated databases. An example reporting sheet is presented that includes relevant metrics, from PR and ROC curves to runtime and carbon footprint, to ensure the models released can be trusted and encourage wider use of PPI imputation for downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is addressed by the PR curve where precision puts an emphasis on positive examples. It has also been shown that ROC tend to overestimate the performance of PPI prediction tools [18], but most published models still report it, which justifies the inclusion of both metrics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we leveraged advances in edge prediction algorithms 19 and AlphaFold-based modeling 20 to evaluate the interaction prediction performance of the panel of interactomes. Using 10-fold crossvalidation with L3 12 (paths of length 3) and MPS(T) 19,47 (Maximum similarity, Preferential attachment Score) algorithms, we predicted interactions for each interactome, excluding interactomes with greater than 1.5M interactions due to computational constraints. The predicted interactions were assessed against held-out and gold-standard interactions.…”
Section: Evaluation and In Silico Validation Of Predicted Interactionsmentioning
confidence: 99%